Rescuing ocular development in an anophthalmic pig by blastocyst complementation - Hongyong Zhang; Jiaojiao Huang; Zechen Li; Guosong Qin; Nan Zhang; Tang Hai; Qianlong Hong; Qiantao Zheng; Ying Zhang; Ruigao Song; Jing Yao; Chunwei Cao; et al. (EMBO Molecular Medicine)
Abstract Porcine‐derived xenogeneic sources for transplantation are a promising alternative strategy for providing organs for treatment of end‐stage organ failure in human patients because of the shortage of human donor organs. The recently developed blastocyst or pluripotent stem cell (PSC) complementation strategy opens a new route for regenerating allogenic organs in miniature pigs. Since the eye is a complicated organ with highly specialized constituent tissues derived from different primordial cell lineages, the development of an intact eye from allogenic cells is a challenging task. Here, combining somatic cell nuclear transfer technology (SCNT) and an anophthalmic pig model (MITFL247S/L247S), allogenic retinal pigmented epithelium cells (RPEs) were retrieved from an E60 chimeric fetus using blastocyst complementation. Furthermore, all structures were successfully regenerated in the intact eye from the injected donor blastomeres. These results clearly demonstrate that not only differentiated functional somatic cells but also a disabled organ with highly specialized constituent tissues can be generated from exogenous blastomeres when delivered to pig embryos with an empty organ niche. This system may also provide novel insights into ocular organogenesis.